Vocabulary acquisition through reading: strategies to facilitate brazilian fifth grade efl student's vocabulary learning - Donato, Rosa Maria Beal (1999)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão.